Analisis Green Brand Knowledge Terhadap Minat Beli Online Melalui E-WOM pada Produk Innisfree di Kota Bandung - Ramadhani, Rahima; Dharma Mangruwa, Rajiv (eProceedings of Management, 2024)
In the current era of globalization, the main issue is the accumulation of plastic waste and the increase in populationthat causes excessive industrial development. Public awareness of the environment is increasing, encouragingcompanies to create green products and implement green marketing strategies. One type of green product in thebeauty sector that implements a green brand is Innisfree with its environmentally friendly products. This study aimsto determine how much influence green brand knowledge has on online purchase intention with e-wom as a mediatorfor Innisfree products in Bandung. The method used is quantitative method. The population in this study amounted to200 samples using non-probability sampling with purposive sampling technique. Data collection using aquestionnaire distributed via Google Form. The data analysis technique used is SEM - PLS with SmartPLS 4.0software. Based on the research results, the green brand knowledge variable has a significant effect on onlinepurchase intention. Green brand knowledge variables have a significant effect on e-wom. The e-wom variable has asignificant effect on online purchase intention. and green brand knowledge has a significant effect on online purchaseintention through e-wom. Keywords-green brand knowledge, online purchase intention, E-WOM